A. Perencanaan Optimal Jumlah Petugas Pada Gerbang Tol Kuningan 2 Dengan Metode Antrian - Lombardo, Doddy -; Rosyidi, Edward (Fakultas Teknik dan LPPM Universitas WR Supratman Surabaya, 2019)
ABSTRACTION   PT Jasa Marga (Persero), Tbk is a company engaged in the development and movement of toll roads having a Current, Safe and Comfortable Quality Policy increasingly demanded to improve the quality of its services. The number of substations that have been repaired at the Kuningan Toll Gate 2 against 4 substations cannot receive currents that increase during rush hour. The queue exceeds the service standards set by the government for a maximum of 5 vehicles for each substation. In this study used the FIFO Queue Model and Distribution testing using the Promodel 7.0 Version of Student Software to find out the distribution of arrival rate and service level data. To test the average value is used the One-way ANOVA test which was previously carried out also the test of adequacy, uniformity and normality of the data. Data collection is taken when a long queue is carried out at the Toll Gate. After passing the test, the next data ? is equal to 2,004 vehicles / hour and ? is = 417 vehicles / hour with Service Time = 8.63 seconds / vehicle, if it is done with Queuing Theory. Results Processing data with queuing theory obtained N (optimal) = 6 and n (Number of vehicles in the system) = 5 vehicles, q (Number of vehicles in queue) = 4 vehicles, d (Time of vehicle in system) = 43.37 seconds, w (Time of vehicle in queue) = 34.74 seconds. The results of data preparation are further processed to obtain optimal Employee Scheduling using tables so that there will be 3 employees in shift 1, 9 in Shift 2 and 2 in shift 3. on weekdays and 3 people on shift 1, 3 on Shift 2 and 2 on shift 3 on holidays. Keywords: Queue Method, Toll Gate, Planning, Optimization